2014
DOI: 10.1007/s10006-014-0474-1
|View full text |Cite
|
Sign up to set email alerts
|

Accessory mental foramen: an anatomical study on dry mandibles and review of the literature

Abstract: The present study revealed an appreciable incidence of the accessory mental foramen in the Greek population, recognizably higher than the discovered incidence of past studies involving the Greek population. Consequently, the clinician should always be prepared to deal with an accessory mental foramen during surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 19 publications
1
30
1
Order By: Relevance
“…Our study revealed an incidence of 5.6% of a double MF, a very near finding to Paraskevas et al [22] results also performed in a Greek population. The MF duplication is explained taking into consideration the MN separation into several fasciculi earlier than MF formation up to the 12 th gestational week [22].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our study revealed an incidence of 5.6% of a double MF, a very near finding to Paraskevas et al [22] results also performed in a Greek population. The MF duplication is explained taking into consideration the MN separation into several fasciculi earlier than MF formation up to the 12 th gestational week [22].…”
Section: Discussionsupporting
confidence: 88%
“…During several surgical procedures, such as genioplasty, mandibular rehabilitation after trauma, root resection of mandibular premolars, dental implants placement and orthognathic procedures, oral and maxillofacial surgeon should be aware of the possibility to encounter an atypically placed MF in the mental area in order to prevent the MN and adjacent blood vessels damage and the resulting postoperative paraesthesia, hypoesthesia, hyperaesthesia, dysaesthesia, or anaesthesia of the teeth, the lower lip, or surrounding skin and mucosa [11,22,35]. The resulting oedema after such compression [24,30] or the haematoma formation (intraneural blood vessels trauma) [32] may also lead to a prolonged and possibly permanent change in sensation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there has been significant interest in the course of the mandibular canal, so as to avoid injury to the critical neurovascular structures within. Consideration of the AMF is highly important during many aspects of clinical dentistry such as local anesthesia and oral surgery, for example, implant, periodontal and endodontic surgery, in order to avoid postoperative sensory disturbances or hemorrhage, which may lead to an unfavorable outcome of the planned treatment (Naitoh et al, ; Cantekin and Şekerci, ; Imada et al, ; Muinelo‐Lorenzo et al, ; Paraskevas et al, ; Torres et al, ; Iwanaga et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…5 The presence and variations of accessory mental foramen is also reported by different researchers. 6,7 Mental foramen is an important landmark at the time of surgical intervention in the mental region of mandible and during local anesthesia. The knowledge of the position of MF is also important for endodontics (root canal treatment and apiecetomy), implant placement, fracture reduction and orthognathic surgery.…”
Section: Introductionmentioning
confidence: 99%